Trajectories of Sexual Satisfaction and Frequency During and After Couple Therapy for Relationship Distress. Issue 3 (3rd April 2021) - Rothman, Karen; Cicila, Larisa N.; McGinn, Meghan; Hatch, S. Gabe; Christensen, Andrew; Doss, Brian D.
Abstract: Using a sample of 134 distressed, different-sex couples, this study investigated the effects of Integrative Behavioral Couple Therapy and Traditional Behavioral Couple Therapy on sexual dissatisfaction and sexual frequency both during treatment and in the five years following treatment. Therapy effects depended on treatment type, gender, and whether sexual distress was identified as a presenting problem; while couple therapy may initially improve some aspects of the sexual relationship, impacts tend to fade over follow-up. Couple therapy may benefit from incorporating a greater emphasis on sex and inclusion of techniques from sex therapy.